POCUS in Intensive Care Nephrology - Randi Connor-Schuler; Jonathan Suarez (CINQUILL Medical Publishers Inc., 2022)
Acute kidney injury (AKI) is a significant problem for patients admitted to the intensive care unit (ICU), both due to the high incidence and associated mortality with rates of AKI requiring renal replacement therapy (RRT) of over 5%, and mortality rates with AKI of over 60% [1,2]. Ultrasound can be used to identify those at risk for AKI and assist with AKI management. Risk factors for AKI in the ICU not only include hypoperfusion but also venous congestion and volume overload. Volume overload and vascular congestion are associated with multi-organ dysfunction and worse renal outcomes. Daily and overall fluid balance, daily weights, and physical examination for edema can be inaccurate and belie true systemic venous pressure [3-5]. Bedside ultrasound allows providers to evaluate vascular flow patterns and obtain a more reliable evaluation of volume status to guide and individualize therapies. Cardiac, lung, and vascular patterns on ultrasound can identify preload responsiveness, which should be assessed to safely manage ongoing fluid resuscitation and assess for signs of fluid intolerance. Here we present an overview in the use of point of care ultrasound with particular emphasis on nephro-centric strategies, namely in the identification of the type of renal injury, renal vascular flow assessment, the static measure of volume status, as well as dynamic evaluation for volume optimization in critically ill patients.